A Novel Design to Eliminate Lüders Band in Medium-Mn Steel and Its Microstructure-Property Relationship - Rendong Liu; Zhiping Hu; Chunqing Lin; Dapeng Yang; Xingli Gu; Xin Xu; Jinyu Guo (Crystals, 2023)
In the current work, we design a novel medium Mn steel with a superior mechanical property and no Lüders band. For industrial applications, a “low Mn addition” chemical composition and two kinds of different annealing processes with various initial microstructures were introduced. Consequently, the sample subjected to full austenitized quenching plus intercritical annealing process exhibited an outstanding mechanical property without the Lüders band. The microstructural evolution and austenite reverted transformation behavior were discussed in detail. In addition, austenite stability was estimated by chemistry stability and mechanical stabilization. It seemed that the austenite stability was significantly influenced by the morphological component. Thus, the sample with single lath-like ferrite and austenite exhibited the most excellent mechanical property. Furthermore, the “Lüders band” phenomenon was considered to rely on the restriction of martensitic recovery and recrystallization by lath-like morphology. The occurrence of the Lüders band was attributed to the low work-hardening ability caused by dynamic recovery. The formation of lath-like morphology could prevent the occurrence and propagation of the Lüders band by increasing the dislocation density and active TRIP effect.